State and Perspectives of Studying of Psychological Determinants of Volunteer Activities - Palkin K.A (Moscow State University of Psychology and Education, 2018)
The article discusses the most common in the world fields of study of the factors that, according to scientists, in varying degrees, are able to influence the participation of people in volunteer activities. The review running characteristic of such research areas as the theory of "human resources" and related theories of democratization, the welfare state, social background; theory of individual personality characteristics of volunteers; attachment theory; identity theory; motivational theories, etc. The focus is psychological components of the personality of the individual, which presumably can be the most important predictors of volunteering. The analysis of a number of studies, made by reputable foreign authors devoted to identifying key determinants of participation in volunteer activities, allows to select among the topical areas one of the most promising - a comprehensive study of psychological characteristics of personality with the goal of creating the most accurate representation of the collective identity of the modern volunteer.